Cerato-platanins: a fungal protein family with intriguing properties and application potential - Gaderer, Romana (Springer Berlin Heidelberg, 2014)
Cerato-platanin proteins are small, secreted proteins with four conserved cysteines that are abundantly produced by filamentous fungi with all types of lifestyles. These proteins appear to be readily recognized by other organisms and are therefore important factors in interactions of fungi with other organisms, e.g. by stimulating the induction of defence responses in plants. However, it is not known yet whether the main function of cerato-platanin proteins is associated with these fungal interactions or rather a role in fungal growth and development. Cerato-platanin proteins seem to unify several biochemical properties that are not found in this combination in other proteins. On one hand, cerato-platanins are carbohydrate-binding proteins and are able to bind to chitin and N-acetylglucosamine oligosaccharides; on the other hand, they are able to self-assemble at hydrophobic/hydrophilic interfaces and form protein layers, e.g. on the surface of aqueous solutions, thereby altering the polarity of solutions and surfaces. The latter property is reminiscent of hydrophobins, which are also small, secreted fungal proteins, but interestingly, the surface-activity-altering properties of cerato-platanins are the opposite of what can be observed for hydrophobins. The so far known biochemical properties of cerato-platanin proteins are summarized in this review, and potential biotechnological applications as well as implications of these properties for the biological functions of cerato-platanin proteins are discussed.